How Customer Engagement Leads to Word-of-Mouth and Continuance Intention? The Mediating Role of Satisfaction - Burhanudin Burhanudin; Raden Roro Windy; Syed Muntasir Husain Bokhari (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
With active participation from halal tourism visitors, managers can comprehend visitors’ needs and expectations. This information can be utilized to enhance services and adapt to tourism requirements. The purpose of this study is to examine the effect of customer engagement on satisfaction, as well as its effect on both continuance intention and word-of-mouth (WOM). Additionally, this study examines the mediation of satisfaction on the effect of customer engagement on continuance intention and the effect of customer engagement on WOM. A survey was conducted to test these effects, involving 250 visitors of Al-Aqsa Holy Tower Mosque, Kudus, Indonesia. Structural equation modeling was employed to analyze the data in this study. The analysis results reveal that customer engagement influences satisfaction, which subsequently affects WOM and continuance intention. In addition, satisfaction mediates the effect of customer engagement on continuance intention and the effect of customer engagement on WOM. These findings indicate that tourism managers can leverage customer engagement to sustain the development of their tourism industry.